PENGARUH OLAHRAGA TERHADAP KESEHATAN MENTAL MAHASISWA / MAHASISWI - Manalu, Nimrot; Devi Uliani Br Saragih; Cathrine Alexsandra Hutahuruk; Anggie Prisilia; Ahmad Pipo Perangin-angin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the influence of exercise on the mental health of university students. Mental health problems such as stress, anxiety, and emotional instability are commonly experienced by students due to academic pressure, social demands, and lifestyle changes. The purpose of this research is to determine the effect of regular physical activity on improving students’ mental health conditions. This study used a quantitative research method with a survey approach involving university students as respondents. Data were collected through questionnaires related to exercise habits and mental health conditions. The results of the study indicate that regular exercise has a positive effect on students’ mental health. Students who actively participate in physical activities tend to have lower levels of stress and anxiety, better emotional control, and higher self-confidence compared to students who rarely exercise. In conclusion, exercise plays an important role in maintaining and improving the mental health of university students. Therefore, students are encouraged to engage in regular physical activity as part of a healthy lifestyle to support both physical and psychological well-being.